The Factors of Completeness Basic Immunization for Children during the COVID-19 Pandemic - Indah Mastikana; Sumiyati Sumiyati; Septi Maisyaroh Ulina Panggabean (JURNAL KEBIDANAN, 2022)
Immunization comes from the word immune, which means immune or resistant. Immunization is a process when an individual's immune system is strengthened to fight an infectious agent. The purpose of this study was to determine the factors that influence the completeness of basic immunization for children during the Covid-19 pandemic. This study is a quantitative study with a cross sectional approach, the population in this study were all mothers or caregivers who had children aged 9-12 months and the sample of this study was 28 people with sampling using the Slovin formula. Based on the statistical test of the relationship between knowledge and completeness of immunization, p-value 0.002, meaning that there is a relationship between knowledge and completeness of immunization. statistical relationship between employment and completeness of immunization obtained p-value of 0.055, which means that there is no relationship between occupation and completeness of immunization. There is a relationship between family income and completeness of immunization.